Noteworthy Cardiac Literature From 2021: Coronary Guideline Change Without New Data, Heart Transplant Donation After Cardiac Death, Covid Effects on Global Cardiac Surgery, and Attempt to Improve Dissection Remodeling. (June 2022) - Hoffman, Jordan R. H.; Higa, Kelly C.; Lin, Yihan; Reece, T. Brett; Cleveland, Joseph C.; Aftab, Muhammad; Rove, Jessica Y.
Cardiac surgery continues to evolve. The last year has been notable for many reasons. The guidelines for coronary revascularization introduced significant discord. The pandemic continues to affect the care on a global scale. Advances in organ procurement and dissection care move forward with better understanding and better technology.